Readers Theatre Might Enhance Students’ Motivation, Fluency Level, and Reading Comprehension In Preparatory Classes - AlShemeili, Aaesha Mohammed (2021)
This study describes a student-based improvement as a mixed method of quantitative and qualitative research on reading the reader's theatre (RT) that might enhance students' fluency, motivation level, and reading comprehension. This research aimed to improve students' fluency, motivation, and reading comprehension through the reader's theatre in the UAE's preparatory classes. The context of the research was in a government school in Ras Al Khaimah, in the United Arab Emirates, and the sample size was five students of the same abilities of motivation and fluency. The methods were students' performance of reader's theatre script twice a week and repeated reading. Date was triangulated for validity and reliability purpose like the reflective journal, self-evaluation checklist, audience-evaluation checklist, motivation questionnaire, interview and reading comprehension with teachers and principal. The major findings were: 1) It Appears that RT can improve students' fluency in preparatory classes 2) It appears that RT can improve students' motivation in preparatory classes 3) it appears that RT can improves student reading comprehension.